Measuring richness and poverty: a micro data application to Europe and Germany - Andreas Peichl; Thilo Schaefer; Christoph Scheicher (Institute for the Study of Labor (IZA), 2008)
In this paper, we define a new class of richness measures. In contrast to the often used headcount, these new measures are sensitive to changes in rich persons' income and therefore allow for a more sophisticated analysis of richness. We demonstrate the application of these new measures to analyze the development of poverty and richness over time in Germany, to compare Germany to many other European countries and to investigate the impact of tax reforms on poverty and richness. Using these examples, we show the importance of taking into account the intensity of changes and not only the number of people beyond a given richness line (headcount). We propose to use the new measures in addition to the headcount index for a more comprehensive analysis of richness.
urn:nbn:de:101:1-20081126543
Keywords: D31; 330; Richness; affluence; poverty; tax reform; flat tax; Reichtum; Armut; Disparitätsmaß; Flat Tax; Steuerreform; Steuerinzidenz; Simulation; Deutschland; Welt